A modified molten-salt method to prepare graphene electrode with high capacitance and low self-discharge rate. (June 2016) - Wang, Jie; Ding, Bing; Hao, Xiaodong; Xu, Yunling; Wang, Ya; Shen, Laifa; Dou, Hui; Zhang, Xiaogang
Abstract: Graphene is known to suffer from severe aggregation and incomplete recovery of a π–π conjugated system during the reduction process from graphene oxide. Here we report that these issues can be addressed by using a modified molten salt system. The advantages of the molten salt for reducing graphene show in three aspects: (i) prevent restacking; (ii) restore the conjugated network; (iii) serve as reaction medium for KNO3 activation and nitrogen doping. The molten-salt method-derived graphene (MNG) displays a highly sp 2 –hybrid constitution, nitrogen doping and hierarchically porous structure. With this design, the MNG–based supercapacitor manifests outstanding specific capacitance (234 F g −1 and 130 F g −1 in 6 M KOH and EMIMBF4 electrolyte, respectively), high power density, combined with excellent cycling stability and low self-discharge rate. The facile and scalable features of this strategy will be helpful for the rational design of functionalized graphene-based materials for diverse applications.